Correction: Developing an advanced gut on chip model enabling the study of epithelial cell/fibroblast interactions. Issue 6 (28th February 2023) - Verhulsel, Marine; Simon, Anthony; Bernheim-Dennery, Moencopi; Gannavarapu, Venkata Ram; Gérémie, Lauriane; Ferraro, Davide; Krndija, Denis; Talini, Laurence; Viovy, Jean-Louis; Vignjevic, Danijela Matic; Descroix, Stéphanie
Abstract : Correction for 'Developing an advanced gut on chip model enabling the study of epithelial cell/fibroblast interactions' by Marine Verhulsel et al., Lab Chip, 2021, 21, 365–377, ; https://doi.org/10.1039/d0lc00672f .